Professional Self-Efficacy in Museum Educators - Bramble, Caitlyn Elizabeth (My University, 2020)
In the 21st century, museum educators are adapting to a changing field and actively considering the meaning of their roles as professionals, and yet there is little research on the topic of professional self-efficacy in museums. The purpose of this phenomenological study was to examine museum educators’ professional self-efficacy. A diverse group of thirty-three practicing museum educators were interviewed, all of whom worked in non-STEM-focused institutions. Leadership strategies, institutional culture, and access to professional development emerged as significant factors in the development of museum educators’ professional efficacy. Study results suggest practices that could be employed by museum studies faculty, mentors of emerging professionals, and others invested in the professionalization of museum educators to support the ongoing development of their colleagues’ confidence to do their jobs.
Thesis (Master's)--University of Washington, 2020
Keywords: Informal Education; Museology; Museum Education; Professional Self-Efficacy; Self-Efficacy; Museum studies; Education; Museology